Evolutionary history inferred from the de novo assembly of a nonmodel organism, the blue‐eyed black lemur - Meyer, Wynn K; Venkat, Aarti; Kermany, Amir R; de Geijn, Bryce; Zhang, Sidi; Przeworski, Molly (Molecular ecology, 2015)
Lemurs, the living primates most distantly related to humans, demonstrate incredible diversity in behaviour, life history patterns and adaptive traits. Although many lemur species are endangered within their native Madagascar, there is no high‐quality genome assembly from this taxon, limiting population and conservation genetic studies. One critically endangered lemur is the blue‐eyed black lemur Eulemur flavifrons. This species is fixed for blue irises, a convergent trait that evolved at least four times in primates and was subject to positive selection in humans, where 5′ regulatory variation of OCA2 explains most of the brown/blue eye colour differences. We built a de novo genome assembly for E. flavifrons, providing the most complete lemur genome to date, and a high confidence consensus sequence for close sister species E. macaco, the (brown‐eyed) black lemur. From diversity and divergence patterns across the genomes, we estimated a recent split time of the two species (160 Kya) and temporal fluctuations in effective population sizes that accord with known environmental changes. By looking for regions of unusually low diversity, we identified potential signals of directional selection in E. flavifrons at MITF, a melanocyte development gene that regulates OCA2 and has previously been associated with variation in human iris colour, as well as at several other genes involved in melanin biosynthesis in mammals. Our study thus illustrates how whole‐genome sequencing of a few individuals can illuminate the demographic and selection history of nonmodel species.